Preparation method of pre-crosslinked gel particles with double-network structure, product and application of pre-crosslinked gel particles
By adopting a dual-network structure pre-crosslinked gel particles preparation method, the problem of insufficient temperature and salt resistance in high-temperature and high-salt reservoirs is solved, and efficient sealing and improving recovery rate in high-temperature and high-salt environments are achieved.
Patent Information
- Application Number
- CN202411913817.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Traditional pre-crosslinked gel particles have insufficient temperature and salt resistance in high-temperature and high-salt reservoirs, which affects the sealing efficiency and is difficult to achieve the expected dissection and water blocking effect.
The pre-crosslinked gel particles with a dual network structure are prepared by dissolving the monomer in water and adding a crosslinking agent and an initiator to react to form a CBCH hydrogel, and immersing it in a tannin solution to form a CBDCH hydrogel, and finally drying and grinding to obtain pre-crosslinked gel particles with a dual network structure.
The gel particles prepared by this method have excellent mechanical properties and temperature and salt resistance, and show high swelling rate and good sealing effect in high temperature and high salt environments, which improves the recovery rate.
Smart Images

Figure CN119708554A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical fields of oilfield chemistry and high-temperature and high-salinity oil reservoir profile control and water plugging, and in particular to a preparation method, product and application of pre-crosslinked gel particles with a double network structure. Background Art
[0002] As oil fields are gradually developed, long-term water flooding leads to the formation of dominant high-permeability channels in the reservoir, and the water-oil ratio gradually increases, increasing the cost of post-processing and separation. At the same time, water flooding will lead to uneven distribution of fluids in the reservoir, resulting in inefficient or even ineffective water flooding cycles, reducing oil recovery efficiency. Pre-cross-linked gel particles can absorb water and swell in the reservoir, effectively blocking high-permeability areas and prompting water to flow to low-permeability areas, thereby increasing crude oil recovery.
[0003] Pre-cross-linked gel particles are a three-dimensional cross-linked polymer network system synthesized indoors. They can be injected into oil reservoirs to plug high-permeability channels, thereby improving water drive sweep efficiency and recovery. However, with the deepening of exploration and development, reservoir conditions continue to deteriorate, and high-temperature and high-salt reservoirs continue to increase. Traditional pre-cross-linked gel particles have insufficient heat and salt resistance, which affects the plugging efficiency and makes it difficult to achieve the expected profile control and water plugging effects. Summary of the invention
[0004] Based on the above content, the present invention provides a preparation method, product and application of pre-crosslinked gel particles with a double network structure to overcome the problems of insufficient mechanical properties and inability to withstand high temperature and high salt environments of existing pre-crosslinked gel particles.
[0005] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is a method for preparing pre-crosslinked gel particles with a double network structure, comprising the following steps:
[0006] The monomer is dissolved in water, and then a cross-linking agent is added to obtain a mixed solution;
[0007] adding an initiator to the mixed solution to react and obtain a CBCH hydrogel;
[0008] The CBCH hydrogel is completely immersed in a tannic acid solution to obtain a CBDCH hydrogel, and then dried and ground to obtain the pre-crosslinked gel particles having a double network structure;
[0009] The monomers are acrylamide, N,N-dimethylacrylamide, acrylic acid and sodium p-styrene sulfonate.
[0010] The second technical solution of the present invention is a pre-crosslinked gel particle with a double network structure prepared according to the preparation method.
[0011] A third technical solution of the present invention is the application of the pre-crosslinked gel particles with a double network structure in profile control and water plugging in high-temperature and high-salinity oil reservoirs.
[0012] A fourth technical solution of the present invention is a profile control and water plugging agent suitable for high-temperature and high-salinity oil reservoirs, the raw materials of which include the pre-crosslinked gel particles with a double network structure.
[0013] The present invention discloses the following technical effects:
[0014] The pre-crosslinked gel particles of the present invention have a unique double network structure and excellent mechanical properties.
[0015] The preparation process of the pre-crosslinked gel particles with a double network structure is simpler, and the pre-crosslinked gel particles have excellent temperature resistance and salt resistance. 4 The gel swelling ratio was 10.29 under the conditions of (mg / L) solution and temperature of 120℃.
[0016] After the pre-crosslinked gel particles with a double network structure of the present invention are injected into the formation as a profile control and water plugging agent, the pre-crosslinked gel particles can block water in the high permeability area, improve the heterogeneity of the formation, increase the water drive swept area, and thus achieve the effect of improving the recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is a schematic diagram of the process flow for preparing pre-crosslinked gel particles with a double network structure according to Example 2.
[0019] Figure 2 SEM images of CBCH hydrogel (a-1, a-2, a-3, a-4) and CBDCH hydrogel (b-1, b-2, b-3, b-4) in Example 2 and the corresponding EDX Mapping images.
[0020] Figure 3 FT-IR images of CBCH and CBDCH hydrogels prepared in Example 2.
[0021] Figure 4 The rheological properties of the CBCH hydrogel and the CBDCH hydrogel in Example 2; wherein (a) the strain scanning range is 0.01% to 1000%; and (b) the frequency scanning range is 0.1 Hz to 10 Hz.
[0022] Figure 5 The uniaxial compression properties of the CBCH hydrogel and the CBDCH hydrogel in Example 2; wherein, (a) the compression stress-strain curve; (b) the corresponding toughness and compression modulus of the CBCH hydrogel and the CBDCH hydrogel.
[0023] Figure 6 This is the plugging performance of the CBDCH gel particles in Example 2. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The first aspect of the present invention provides a method for preparing pre-crosslinked gel particles having a double network structure, comprising the following steps:
[0030] The monomer is dissolved in water, and then a cross-linking agent is added to obtain a mixed solution;
[0031] adding an initiator to the mixed solution to react and obtain a CBCH hydrogel;
[0032] The CBCH hydrogel is completely immersed in a tannic acid solution to obtain a CBDCH hydrogel, and then dried and ground to obtain the pre-crosslinked gel particles having a double network structure;
[0033] The monomers are acrylamide, N,N-dimethylacrylamide, acrylic acid and sodium p-styrene sulfonate.
[0034] In a preferred embodiment of the present invention, the mass ratio of acrylamide, N,N-dimethylacrylamide, acrylic acid and sodium styrene sulfonate is 4:4:3:1; the amount of the monomer added is 20wt%-30wt% of the water. Acrylamide and N,N-dimethylacrylamide are the main cross-linking monomers, which help to adjust the mechanical strength, stability and hydrophilicity of the gel respectively. Acrylic acid (AcrylicAcid) as a hydrophilic monomer can significantly improve the swelling properties of the gel through the dissociation effect of its carboxyl group. Sodium styrene sulfonate (Sodium Styrene Sulfonate) significantly enhances the thermal stability and temperature and salt resistance of the gel in a complex reservoir environment through its rigid benzene ring group and salt resistance. Its sulfonic acid group dissociates in an aqueous solution to produce a negative charge, giving the gel good ion exchange capacity and a strong charge density, thereby improving its performance under extreme conditions, especially in high temperature and high salt environments. In the design of monomer ratio, too high a cross-linking monomer ratio may lead to too high a cross-linking density of the gel, which in turn affects the swelling properties and mechanical strength of the gel, and may also increase the brittleness of the gel and reduce its toughness; while too low a monomer ratio may lead to a loose structure of the gel, reduce its mechanical strength and stability, and may even affect the formation of the double network structure, making it impossible to effectively achieve the expected multifunctionality. Therefore, the optimization design of the reasonable monomer types and ratios is a key factor in ensuring the stability of the double network structure and the excellent comprehensive performance of the gel particles.
[0035] In summary, the type and ratio of monomers not only affect the structural characteristics and physical properties of the gel, but also determine the performance of the gel in a specific environment. The reasonable design of the monomer ratio and monomer content proposed in the present invention can effectively balance the swelling, mechanical properties and environmental resistance of the gel. By accurately controlling the ratio of each monomer, the cross-linking density of the gel can be optimized, thereby achieving an ideal double network structure and ensuring that the gel has excellent comprehensive performance under different environmental conditions.
[0036] In a preferred embodiment of the present invention, the crosslinking agent is methacrylated chitosan; the initiator is at least one of potassium persulfate, ammonium persulfate and azobisisobutylimidazoline hydrochloride; the added amount of the crosslinking agent is 1wt% of the mixed solution; the added amount of the initiator is 1wt% of the mixed solution.
[0037] In the present invention, the green cross-linking agent methacrylated chitosan (ChMA) is used to replace the traditional cross-linking agent MBA. First, ChMA reacts with the monomer to form a hydrogel network with a chemical cross-linking structure, and then is immersed in a tannic acid (TA) solution. By forming a large number of hydrogen bonds with the hydrogel molecular chains, the hydrogel is further endowed with a reversible physical cross-linking dynamic network. The hydrogel with this double network structure has excellent mechanical properties. The dynamic physical cross-linking network can be effectively de-cross-linked under the action of external force to dissipate energy, and quickly recover by restoring the reversible cross-linking bonds after the pressure disappears. At the same time, the chemical cross-linking network ensures the structural integrity of the hydrogel. This pre-cross-linked gel particle plugging agent with a double network structure has good stability and excellent strength under high temperature and high salt conditions, and can be better applied to high temperature and high salt reservoir profile control and water plugging.
[0038] In a preferred embodiment of the present invention, before adding the initiator to the mixed solution, the step of introducing nitrogen into the mixed solution to remove oxygen in the mixed solution is also included; the reaction temperature is 45-65°C and the reaction time is 4-6h.
[0039] In a preferred embodiment of the present invention, the solvent of the tannic acid solution is water; the concentration of the tannic acid solution is 0.05-0.2 mmol / L; and the immersion time is 8-12 hours.
[0040] The second aspect of the present invention provides pre-crosslinked gel particles having a double network structure prepared according to the preparation method.
[0041] The third aspect of the present invention provides the use of the pre-crosslinked gel particles with a double network structure in profile control and water plugging in high-temperature and high-salinity oil reservoirs.
[0042] A fourth aspect of the present invention provides a profile control and water plugging agent suitable for high-temperature and high-salinity oil reservoirs, the raw materials of which include the pre-crosslinked gel particles having a double network structure.
[0043] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0044] The methacrylated chitosan (ChMA) used in the embodiment of the present invention is homemade in the laboratory, and the preparation steps of methacrylated chitosan are as follows:
[0045] First, 3% (w / v) chitosan powder was dissolved in 3% (v / v) acetic acid solution at room temperature (RT) overnight. Methacrylic anhydride was added to the mixed solution in a mass ratio of 4:1 to chitosan, and reacted at room temperature for 4 hours under the action of a magnetic stirrer. After the reaction was completed, the reaction mixture was further purified with deionized water using a cellulose dialysis membrane (molecular weight cutoff of 14 kDa), and the resulting mixture was then freeze-dried in a vacuum freeze dryer to obtain ChMA, which was then stored in a refrigerator for standby use. ChMA obtained by other means, such as purchase, is also applicable to the present invention.
[0046] The test methods involved in the present invention: the swelling rate test refers to the GB / T 1033.1-2008 standard, the rheological property test refers to the ISO 11443:2006 standard, and the uniaxial compression property test refers to the GB / T 1041-2008 standard.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] A method for preparing pre-crosslinked gel particles with a double network structure, comprising the following steps:
[0050] (1) 4 g of acrylamide, 4 g of N,N-dimethylacrylamide, 3 g of acrylic acid and 1 g of sodium p-styrene sulfonate were dissolved in 48 mL of deionized water and stirred with a magnetic stirrer to completely dissolve. Then, 0.12 g of green crosslinking agent methacrylated chitosan was added to the above solution, and nitrogen was injected for 15 min to remove oxygen in the solution to obtain a mixed solution.
[0051] (2) 0.12 g of potassium persulfate was added to the mixed solution, and after stirring to completely dissolve it, the mixture was poured into a glass bottle and transferred to a 45° C. forced air drying oven for reaction for 4 h to obtain a ChMA-crosslinked hydrogel (CBCH hydrogel).
[0052] (3) The prepared CBCH was cut into uniform disc-shaped samples, and then immersed in a 0.05 mmol / L tannic acid solution overnight (8-12 hours, the CBCH gel must be completely immersed in the tannic acid solution) to prepare a ChMA-based double cross-linked hydrogel (CBDCH hydrogel), which was dried at 60°C for 12 hours and then crushed and ground through a 100-mesh sieve to obtain pre-cross-linked gel particles with a double network structure.
[0053] The CBDCH hydrogel prepared in this example was heated to 10% NaCl (10×10 4The swelling kinetics of CBDCH hydrogel at different temperatures (60℃, 80℃, 100℃ and 120℃) were 1.15, 4.33, 6.12 and 7.02 respectively. 4 mg / L of formation water; the formation contains various inorganic salts, so the mineralization of the formation water is very high, 22×10 4 mg / L in formation water 4 mg / L represents the concentration of various inorganic salt ions in formation water), and their swelling rates are 3.34, 2.28, 1.13, 1.04 and 0.91 respectively.
[0054] Example 2
[0055] A method for preparing pre-crosslinked gel particles with a double network structure, comprising the following steps:
[0056] (1) Same as step (1) of Example 1.
[0057] (2) 0.12 g of potassium persulfate was added to the mixed solution, and after stirring to completely dissolve it, the mixture was poured into a glass bottle and transferred to a 55° C. forced air drying oven for reaction for 4 h to obtain a ChMA-crosslinked hydrogel (CBCH hydrogel).
[0058] (3) The prepared CBCH gel sample was cut into uniform disc-shaped samples, and then immersed in a 0.05 mmol / L tannic acid solution overnight to prepare a ChMA-based double cross-linked hydrogel (CBDCH hydrogel), which was dried at 60°C for 12 h and then crushed and ground through a 100-mesh sieve to obtain pre-cross-linked gel particles with a double network structure.
[0059] The schematic diagram of the process flow for preparing pre-crosslinked gel particles with a double network structure in this embodiment is as follows: Figure 1 shown.
[0060] Figure 2 is the SEM image of CBCH hydrogel and CBDCH hydrogel; Figure 2 It can be seen that the CBCH gel presents an ordered porous structure, which is derived from the uniform three-dimensional network formed by the crosslinker ChMA and the monomer under the action of the initiator. Figure 2 a-4) shows that C, N, O, and S elements are evenly distributed in the gel, verifying the uniformity of the cross-linked network. Figure 2b shows that after TA modification, the CBDCH gel network is tighter, the pores are smaller and denser. Compared with CBCH, the content of C, N and O elements in CBDCH increased significantly and the distribution was more uniform. The results show that TA enhances the entanglement between polymer chains through hydrogen bonds and promotes the formation of a stable double cross-linked network.
[0061] Figure 3 FT-IR images of CBCH hydrogel and CBDCH hydrogel; Figure 3 It can be seen that in the FTIR spectrum of CBCH, 1664cm -1 C=O stretching vibration, 1254cm -1 and 1450cm -1 They are CO bending vibration and -OH stretching vibration, 1120cm -1 The FTIR spectrum of CBDCH overlaps with that of TA, indicating that TA is successfully integrated into the CBCH network. In particular, the phenolic hydroxyl group (3350 cm -1 ) forms hydrogen bonds with functional groups such as amide and carboxyl in CBCH, causing the relevant vibration peaks to shift to lower wavenumbers.
[0062] Figure 4 is the rheological properties of CBCH hydrogel and CBDCH hydrogel (Linear viscoelastic region in the figure represents the linear viscoelastic region); Figure 4 It can be seen that when the strain is less than 10%, the modulus of CBCH and CBDCH samples remains stable, and the elastic modulus (G′) is always higher than the viscous modulus (G″), showing a solid-like behavior and forming a cross-linked three-dimensional network. Figure 4 As shown in (b), the elastic modulus of CBDCH (G′≈12000Pa) is significantly higher than that of CBCH (G′≈7000Pa), an increase of 71.4%, indicating that CBDCH has higher deformation capacity and shear strength.
[0063] Figure 5 is the uniaxial compression performance of CBCH hydrogel and CBDCH hydrogel (Compression Modulus represents compression modulus, and Toughness represents toughness); Figure 5 It can be seen that the compressive strength of CBCH hydrogel at 90% strain is 0.075MPa, while that of CBDCH is 0.124MPa, which is 1.65 times that of CBCH. The enhanced mechanical properties of CBDCH are attributed to the non-covalent cross-linked network formed between TA and hydrophilic monomers, which constructs a double cross-linked structure and improves the cross-linking density and compressive resistance of the gel. Figure 5(b) shows that the compression modulus and toughness of CBDCH hydrogel are 6.87 KPa and 1.63 MJ·m -3 , which are 1.55 and 1.46 times that of CBCH, respectively. The results show that the double cross-linked structure of CBDCH improves the mechanical strength and water absorption capacity, helps to effectively disperse the external force, avoid rupture, and thus improve the plugging efficiency.
[0064] The CBDCH hydrogel prepared in this example was heated to 10% NaCl (10×10 4 The swelling kinetics of CBDCH hydrogel at 80°C and in solutions of different salinities (10% NaCl, 20% NaCl, 25% NaCl, 10% MgCl2+10% CaCl2 and 22×10 4 mg / L formation water), and their swelling ratios were 5.75, 3.53, 1.60, 1.41 and 1.26, respectively.
[0065] Example 3
[0066] The only difference from Example 2 is that the reaction temperature in step (2) is 65° C.; the remaining steps and parameters are the same as in Example 2.
[0067] The CBDCH hydrogel prepared in this example was heated to 10% NaCl (10×10 4 The swelling kinetics of CBDCH hydrogel at different temperatures (60℃, 80℃, 100℃ and 120℃) were 1.22, 4.46, 7.03 and 7.78 respectively. 4 mg / L formation water), and their swelling ratios were 3.86, 1.69, 1.36, 1.11 and 0.97, respectively.
[0068] Example 4
[0069] The only difference from Example 2 is that the concentration of the tannic acid solution in step (3) is 0.1 mmol / L; the remaining steps and parameters are the same as those in Example 2.
[0070] The CBDCH hydrogel prepared in this example was heated to 10% NaCl (10×10 4The swelling kinetics of CBDCH hydrogel at 80℃ and in solutions of different salinities (10% NaCl, 20% NaCl, 25% NaCl, 10% MgCl2+10% CaCl2, 22×10 4 mg / L formation water), and their swelling ratios were 2.65, 0.66, 0.73, 1.18 and 1.69, respectively.
[0071] Example 5
[0072] The only difference from Example 2 is that the potassium persulfate in step (2) is replaced by azobisisobutylimidazoline hydrochloride, and the concentration of the tannic acid solution in step (3) is 0.1 mmol / L; the remaining steps and parameters are the same as in Example 2.
[0073] The CBDCH hydrogel prepared in this example was heated to 10% NaCl (10×10 4 The swelling kinetics of CBDCH hydrogel at different temperatures (60℃, 80℃, 100℃ and 120℃) were 0.75, 1.73, 2.86 and 3.79 respectively. 4 mg / L formation water), and their swelling ratios were 2.19, 0.45, 0.59, 0.97 and 1.68, respectively.
[0074] Plugging performance test:
[0075] The experiment used a natural core with a diameter of 2.49 cm and a length of 4.98 cm for fracture design, and created a rough fracture surface through the Brazilian splitting test. In order to produce a 0.5 mm crack in the core and avoid closure, stainless steel plates were clamped on both sides of the core, and holes were drilled at the entrance to improve injection capacity. The experimental steps are as follows:
[0076] (1) Place the broken core in a holder and load the surrounding pressure to keep it 3 MPa higher than the injection pressure. Inject 2% NaCl solution at a rate of 0.5 mL / min until the injection pressure and flow rate are stable. Calculate the permeability before plugging (K) using Darcy's law. b ).
[0077] (2) Inject 2% gel particle solution (carried by guar gum) at the same injection rate until the injection pressure stabilizes and the particles are observed to flow out from the outlet, then stop the injection. Raise the core temperature to 80°C and age for 24 hours.
[0078] (3) Re-inject 2% NaCl solution at a rate of 0.5 mL / min until the pressure and flow rate are stable, and recalculate the permeability after plugging (K a ). The plugging effect of hydrogel particles was evaluated by breakthrough pressure gradient and plugging efficiency (E).
[0079] E=(K b -K a ) / K b ×100 (1)
[0080] The plugging performance of the CBDCH gel particles in Example 2 was tested, and the results were as follows: Figure 6 To evaluate the sealing effect of reservoir fractures, 0.5 mm steel plates were added to the natural cores to simulate fractures and filled with 100 mesh CBDCH gel particles. Figure 6 It shows that when 2wt% NaCl solution was injected for the first time, the fractures caused high permeability and stable pressure changes. After the injection of CBDCH gel particles, the injection pressure quickly rose to a maximum value (180psi / ft), and then the pressure dropped and stabilized at 157psi / ft as the particles flowed out. The core temperature was raised to 80°C, and the gel particles expanded further. After the second injection of NaCl solution, the breakthrough pressure gradient was 261psi / ft and the stable pressure gradient was 206psi / ft. The plugging efficiency after the injection of CBDCH was 95.4%, and the plugging rate increased to 96.7% after the second injection of NaCl solution. The results show that CBDCH gel particles can effectively plug the high permeability layer and expand at high temperature to form a stable plug.
[0081] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing pre-crosslinked gel particles having a double network structure, characterized in that: The following steps are involved: The monomer is dissolved in water, and then a cross-linking agent is added to obtain a mixed solution; adding an initiator to the mixed solution to react and obtain a CBCH hydrogel; The CBCH hydrogel is completely immersed in a tannic acid solution to obtain a CBDCH hydrogel, and then dried and ground to obtain the pre-crosslinked gel particles having a double network structure; The monomers are acrylamide, N,N-dimethylacrylamide, acrylic acid and sodium p-styrene sulfonate.
2. The preparation method according to claim 1, characterized in that: The mass ratios of acrylamide, N,N-dimethylacrylamide, acrylic acid and sodium p-styrene sulfonate are 4:4:3:1 respectively; and the added amount of the monomer is 20wt%-30wt% of the water.
3. The preparation method according to claim 1, characterized in that: The cross-linking agent is methacrylated chitosan; the initiator is at least one of potassium persulfate, ammonium persulfate and azobisisobutylimidazoline hydrochloride; the added amount of the cross-linking agent is 1wt% of the mixed solution; the added amount of the initiator is 1wt% of the mixed solution.
4. The preparation method according to claim 1, characterized in that: Before adding the initiator to the mixed solution, the method further comprises introducing nitrogen into the mixed solution to remove oxygen in the mixed solution; the reaction temperature is 45-65° C. and the reaction time is 4-6 hours.
5. The preparation method according to claim 1, characterized in that: The solvent of the tannic acid solution is water; the concentration of the tannic acid solution is 0.05-0.2 mmol / L; and the immersion time is 8-12 hours.
6. Pre-crosslinked gel particles with a double network structure prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the pre-crosslinked gel particles with a double network structure as claimed in claim 6 in profile control and water plugging in high-temperature and high-salinity oil reservoirs.
8. A profile control and water plugging agent suitable for high-temperature and high-salinity oil reservoirs, characterized in that: The raw materials include the pre-crosslinked gel particles with a double network structure as described in claim 6.
Citation Information
Patent Citations
Tannic acid functionalized photo-crosslinking hydrogel scaffold and preparation method thereof
CN111533940A